Experimental Study on Flexural Performance of Reinforced Concrete Beams with Lap Splices and Threaded Coupler-type Mechanical Splice - Jafar,; Yulianto, Hariadi; Ambarwati, Zaneta; Musyaffa, M Firzaki (International Journal of Integrated Engineering, 2025)
This study aimed to assess the feasibility of mechanical splicing as an alternative to traditional lap splicing in reinforced concrete (RC) beams. Six RC beams, including a control beam, a lap-spliced beam, and a mechanically spliced beam using threaded couplers, were subjected to two-point load tests. While the lap-spliced beam exhibited the highest load-carrying capacity, the control beam demonstrated superior ductility, as indicated by higher deflection. The mechanically spliced beams, on the other hand, displayed inferior flexural performance compared to both the control and lap-spliced beams. This reduced performance was attributed to the decreased cross-sectional area of the rebars due to threading and the limited strain distribution caused by the short coupler sleeve. Consequently, this study concludes that lap splicing remains a more effective method for achieving desired levels of flexural strength and ductility in RC beams, and threaded coupler splicing, in its current form, is not a suitable replacement.